How much green does it take to be orange? Determining the cost associated with trauma center readiness. Issue 5 (May 2019) - Ashley, Dennis W.; Mullins, Robert F.; Dente, Christopher J.; Johns, Tracy J.; Garlow, Laura E.; Medeiros, Regina S.; Atkins, Elizabeth V.; Solomon, Gina; Abston, Dena; Ferdinand, Colville H.
Abstract : BACKGROUND: Readiness costs are real expenses incurred by trauma centers to maintain essential infrastructure to provide emergent services on a 24/7 basis. Although the components for readiness are well described in the American College of Surgeons' Resources for Optimal Care of the Injured Patient, the cost associated with each component is not well defined. We hypothesized that meeting the requirements of the 2014 Resources for Optimal Care of the Injured Patient would result in significant costs for trauma centers. METHODS: The state trauma commission in conjunction with trauma medical directors, program managers, and financial officers of each trauma center standardized definitions for each component of trauma center readiness cost and developed a survey tool for reporting. Readiness costs were grouped into four categories: administrative/program support staff, clinical medical staff, in-house operating room, and education/outreach. To verify consistent cost reporting, a financial auditor analyzed all data. Trauma center outliers were further evaluated to validate variances. All level I/level II trauma centers (n = 16) completed the survey on 2016 data. RESULTS: Average annual readiness cost is US $10, 078, 506 for a level I trauma center and US $4, 925, 103 for level IIs. Clinical medical staff was the costliest component representing 55% of costs for level Is and 64% for level IIs. Although education/outreach is mandated, levels I and II trauma centers only spend approximately US $100, 000 annually on this category (1%–2%), demonstrating a lack of resources. CONCLUSION: This study defines the cost associated with each component of readiness as defined in the Resources for Optimal Care of the Injured Patient manual. Average readiness cost for a level I trauma center is US $10, 078, 506 and US $4, 925, 103 for a level II. The significant cost of trauma center readiness highlights the need for additional trauma center funding to meet the requirements set forth by the American College of Surgeons. LEVEL OF EVIDENCE: Economic and value-based evaluations, level III. Abstract : Supplemental digital content is available in the text.